Differentiation of Human iPS Cells Into Sensory Neurons Exhibits Developmental Stage-Specific Cryopreservation Challenges - Li, Rui; Walsh, Patrick; Truong, Vincent; Petersen, Ashley; Dutton, James R.; Hubel, Allison (Frontiers in Cell and Developmental Biology, 2021)
Differentiation of human induced pluripotent stem cells (hiPSCs) generates cell phenotypes valuable for cell therapy and personalized medicine. Successful translation of these hiPSC-derived therapeutic products will rely upon effective cryopreservation at multiple stages of the manufacturing cycle. From the perspective of cryobiology, we attempted to understand how the challenge of cryopreservation evolves between cell phenotypes along a hiPSC-to-sensory neuron differentiation trajectory. Cells were cultivated at three different stages to represent intermediate, differentiated, and matured cell products. All cell stages remained ≥90% viable in a dimethyl sulfoxide (DMSO)-free formulation but suffered ≥50% loss in DMSO before freezing. Raman spectroscopy revealed higher sensitivity to undercooling in hiPSC-derived neuronal cells with lower membrane fluidity and higher sensitivity to suboptimal cooling rates in stem cell developmental stages with larger cell bodies. Highly viable and functional sensory neurons were obtained following DMSO-free cryopreservation. Our study also demonstrated that dissociating adherent cultures plays an important role in the ability of cells to survive and function after cryopreservation.